The Republic of Kazakhstan and the Republic of Korea: mentality in postclassical paradigm - Оh Lee Jong; Myamesheva, G.; Kindikbayeva, K. K. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2018)
This article explores the mentality of the countries of the Republic of Kazakhstan and the Republic of Korea, and compares the mentality of the countries of Kazakhstan and Korea. The purpose of this study is to determine the role of mentality in the modernization of countries. A particular feature of this study is the study not only of the main components of the mentality, but also the consideration of the visual image of countries, the use of a socionic model in determining the mentality. The importance of this research at the theoretical and practical levels is the prospect of using this material to study the relationships between these countries, this material is important not only at the macro level, but also at the micro level. That is, the importance of research is needed at the international and individual level for a more mild and effective entry into the cultural environment of Kazakhstan and Korea. Key words: Kazakhstan, Korea, mentality, culture, society.